2021
DOI: 10.1001/jamanetworkopen.2021.23512
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Women and Underrepresented Groups in US Academic Medicine by Specialty

Abstract: mixed-effects models were used to estimate the mean change per year in percentages of women and percentages of underrepresented in medicine individuals and included department, time, and a department by time interaction, with an autoregressive AR(1) correlation structure for the repeated measures.d P value comparing slope to zero was < .003 for all comparisons.e P value comparing slope to zero < .003.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Our results are consistent with prior published data regarding gender distribution in radiology in North America. 3,5 To our knowledge, this paper is the first to demonstrate marked variation in gender distribution between individual teaching institutions.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our results are consistent with prior published data regarding gender distribution in radiology in North America. 3,5 To our knowledge, this paper is the first to demonstrate marked variation in gender distribution between individual teaching institutions.…”
Section: Discussionmentioning
confidence: 68%
“…3 Similar statistics have been shown at medical schools in the United States, with women representing 29.6% of radiology faculty. 5 Within radiology, many subspecialties are composed of well over two-thirds male radiologists. [6][7][8][9] A 2018 review of academic musculoskeletal radiologists found that 69.34% were men and 30.66% were women.…”
Section: Introductionmentioning
confidence: 99%
“…Those who identify as African American/Black, Hispanic/Latino, American Indian/Alaska Native or Native Hawaiian/Pacific Islander have been considered underrepresented in medicine (URiM) by the Association of American Medical Colleges (AAMC) since 2004. Seventeen years later, it is estimated that only 11.3% of Pediatric faculty at academic health centers (AHCs) are considered URiM (Yoo et al, 2021 ), and among trainees, only 16.5% of residents and 13.5% of fellows are in this category (Montez et al, 2021 ). Regarding other professionals employed by AHCs, recent data indicates that most medical assistants (48.9%; “Medical assistants,” 2020 ) and registered nurses (68.4%; “Registered nurses,” 2020 ) in the United States are White.…”
mentioning
confidence: 99%
“…For women, there has been a substantial increase across various clinical disciplines in the last three decades (1990-2019), including pediatrics [10]. The factors for higher numbers of female pediatric residents are flexibility with job selection, geographic location, autonomy over working hours, more scholarly and educational endeavors, and part-time opportunities [17].…”
Section: Discussionmentioning
confidence: 99%
“…Women and URiM are underrepresented in medical leadership, they are given less funding than their counterparts for research/grants, and they are promoted at lower rates. They are more likely to experience implicit and explicit bias, reduced career flexibility, and isolation and exclusion from opportunities to advance in medical careers [9,10].…”
Section: Introductionmentioning
confidence: 99%